2015
DOI: 10.1186/s40781-015-0043-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forage level and chromium-methionine chelate supplementation on performance, carcass characteristics and blood metabolites in Korean native (Hanwoo) steers

Abstract: A feeding trial was carried out to determine the effects of chromium methionine (Cr-Met) chelate and forage level over two years, 1st fattening and 2nd fattening period on growth parameters, carcass characteristics and blood metabolites of 46 Korean native (Hanwoo, Bos Taurus, BW = 183 ± 44 kg) steers. Treatments were: 1) Steers in the low forage (LF) group were fed diets that consisted of 60% concentrate and 40% forage; 2) Steers in the high forage (HF) group were fed diets that consisted of 40% concentrate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 19 publications
(32 reference statements)
6
32
1
Order By: Relevance
“…Ohh and Lee (2005) concluded that Cr-Met supplementation may not improve body weight of animals. However, by contrast, it has been reported that a higher forage ratio may lead to lower DM intake and lower weight gain in steers in a longer period of growth (Song et al, 2013;Sung et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Ohh and Lee (2005) concluded that Cr-Met supplementation may not improve body weight of animals. However, by contrast, it has been reported that a higher forage ratio may lead to lower DM intake and lower weight gain in steers in a longer period of growth (Song et al, 2013;Sung et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…The meat fatty acid composition has a promising role in the quality of beef for consumers (Lindemann et al, 2008;Sung et al, 2015;Ghassemi Nejad et al, 2016). Chromium can influence fat mobilization from body stores to meet nutrient requirements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations